XIX. Yüzyıl Sonlarında ve XX. Yüzyıl Başlarında Ermenek’in İdarȋ Yapısı / Administration Structure of Ermenek at the end of XIX’th Century and at the Begining of XX’th Century - Sarıköse, Barış (Journal of History Culture and Art Research, 2018)
Abstract Ermenek which was located in Seljuk in the period of Turkey Seljuk State, took part in the border’s of Karamanoğulları Principality after the collapsed fo Turkey Seljuk State. Ermenek and it’s surroundings where connected to Ottoman State after Karamanoğulları Principality was ended by Ottoman State. Ermenek took part in İç-il Sanjak of Karaman Principality in the tahrir of 1530 in the period of Sultan Süleyman I. Ermenek has taken Karaman Principality for long centuries. New regulations were done about the administration of province of Ottoman State with 1864 and 1871 regulations in the XIX’th century. In context some new regulations were made about the administration of Ermenek which took part in İç-il Sanjak of Konya Province. İç-il liva which was connected to Konya Province before was connected to Adana Province. By means of this administration regulations from 1870’s to beginning of XX’th centuries. Ermenek stayed connected to Adana Province. In the beginning of XX’th centuries Ermenek was reconnected to Konya Province. District council and municipality council had established depend on this administrative regulations. Thus people had the opportunity to participate in local government. New administrative units had established and a lot of civil servants had employed in this administrative units. Regulations had made in tax, population record, law and land register field according to new administrative of district in Ermenek. Some new administrative regulations had made on villages administrative status in this period. Ermenek’s village structure at the end of XIX’th century had created the village’s structure in the period of Republic. In this research administrative regulations which were at the end of XX’th and the beginning of the XX’th century and new civil servants and administration units about administrative structure were according to the archival documents. Öz Türkiye Selçuklu Devleti döneminde Selçuklu sınırları içinde yer alan Ermenek, Türkiye Selçuklu Devleti’nin yıkılmasından sonra Karamanoğulları Beyliği sınırları içine girmiştir. Osmanlı Devleti’nin Karamanoğulları Beyliği’ne son vermesi ile Ermenek ve çevresi Osmanlı Devleti’ne bağlanmıştır. Ermenek, Kanuni Sultan Süleyman Dönemi’nde 1530’da yapılan tahrirlerde Karaman Eyaleti İç-il Livası sınırları içinde yer almaktadır. Ermenek, uzun asırlar Karaman Eyaleti sınırları içinde yer almıştır. XIX. yüzyılda Osmanlı Devleti’nin vilayet idaresinde 1864 ve 1871 nizamnȃmeleriyle yeni düzenlemeler yapılmıştır. Bu bağlamda Konya Vilayeti İç-il Livası sınırları içinde yer alan Ermenek’in idarȋ yapısında da birtakım değişiklikler yaşanmıştır. Daha önce Konya Vilayeti’ne bağlı olan İç-il Livası Adana Vilayeti’ne bağlanmıştır. Bu idarî düzenlemeler çerçevesinde Ermenek 1870’li yıllardan XX. yüzyıl başına kadar Adana Vilayeti’ne bağlı kalmıştır. Ermenek, XX. yüzyılın başında tekrar Konya Vilayeti’ne bağlanmıştır. İdarî düzenlemelere bağlı olarak Ermenek’te kaza idare meclisi ve belediye meclisi kurulmuştur. Böylelikle halkın yerel yönetime katılması yönünde önemli bir adım atılmıştır. Bu süreçte Ermenek’te yeni idarî birimler kurulmuş bu birimler de birçok yeni memur istihdam edilmiştir. Ermenek’te vergi, nüfus kaydı, hukuk ve tapu kaydı gibi alanlarda yeni vilayet idaresine göre düzenlemeler yapılmıştır. Bu dönemde Ermenek’e bağlı köylerin idarî durumlarında da birtakım idarî değişiklikler yapılmıştır. Ermenek’in XIX. yüzyıldaki köy yapısı Cumhuriyet dönemindeki köy yapısının temellerini oluşturmuştur. Bu araştırmada Ermenek’in, XIX. yüzyıl sonlarında ve XX. yüzyıl başlarında geçirmiş olduğu idarî değişim ve idarî yapıda ortaya çıkan yeni birim ve memuriyetler arşiv belgelerine göre değerlendirilecektir.